Quantitative single-photon emission computed tomography/computed tomography for technetium pertechnetate thyroid uptake measurement. Issue 27 (July 2016) - Lee, Hyunjong; Kim, Ji Hyun; Kang, Yeon-koo; Moon, Jae Hoon; So, Young; Lee, Won Woo
Abstract : Supplemental Digital Content is available in the text Abstract: Objectives: Technetium pertechnetate ( 99m TcO4 ) is a radioactive tracer used to assess thyroid function by thyroid uptake system (TUS). However, the TUS often fails to deliver accurate measurements of the percent of thyroid uptake (%thyroid uptake) of 99m TcO4 . Here, we investigated the usefulness of quantitative single-photon emission computed tomography/computed tomography (SPECT/CT) after injection of 99m TcO4 in detecting thyroid function abnormalities. Materials and methods: We retrospectively reviewed data from 50 patients (male:female = 15:35; age, 46.2 ± 16.3 years; 17 Graves disease, 13 thyroiditis, and 20 euthyroid). All patients underwent 99m TcO4 quantitative SPECT/CT (185 MBq = 5 mCi), which yielded %thyroid uptake and standardized uptake value (SUV). Twenty-one (10 Graves disease and 11 thyroiditis) of the 50 patients also underwent conventional %thyroid uptake measurements using a TUS. Results: Quantitative SPECT/CT parameters (%thyroid uptake, SUVmean, and SUVmax) were the highest in Graves disease, second highest in euthyroid, and lowest in thyroiditis ( P  < 0.0001, Kruskal–Wallis test). TUS significantly overestimated the %thyroid uptake compared with SPECT/CT ( P  < 0.0001, paired t test) because other 99m TcO4 sources in addition to thyroid, such as salivary glands and saliva, contributed to the %thyroid uptake result by TUS, whereas %thyroid uptake, SUVmean and SUVmax from the SPECT/CT were associated with the functional status of thyroid. Conclusions: Quantitative SPECT/CT is more accurate than conventional TUS for measuring 99m TcO4 %thyroid uptake. Quantitative measurements using SPECT/CT may facilitate more accurate assessment of thyroid tracer uptake.